2013
DOI: 10.5198/jtlu.v6i3.311
|View full text |Cite
|
Sign up to set email alerts
|

Measuring transportation at a human scale: An intercept survey approach to capture pedestrian activity

Abstract: Pedestrian travel data are critical for measuring and analyzing sustainable transportation systems. However, traditional household travel surveys and analysis methods often ignore secondary modes, such as walking from a street parking space to a store entrance or walking from a bus stop to home. New data collection and analysis techniques are needed, especially in areas where walking is common. This paper describes an intercept survey methodology used to measure retail pharmacy customer travel to, from, and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
1
11
0
1
Order By: Relevance
“…Better data on trip length distribution and trip origins and subsequent destinations can help understand the relationships between the market area of an establishment, the distances traveled by visitors, and their modes, all of which have a strong relationship with socioeconomics. As the calls for more and better establishment-level data increase Schneider, 2013;Dock et al, 2015), including socioeconomic and -demographic information about the transportation system users, it is critical to include these data to increase our understanding of trip generation. Table B19013; 2 2010 Census, Summary File 1 (SF1), Table P2; 3 2013 ACS, 5-year summary, Table B17010; 4 2010 Census, SF1, Table H13; 5 2013 ACS, 5-year summary, Table B99051; 6 2010 ACS, 5-year summary, Table B25044 4…”
Section: People Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…Better data on trip length distribution and trip origins and subsequent destinations can help understand the relationships between the market area of an establishment, the distances traveled by visitors, and their modes, all of which have a strong relationship with socioeconomics. As the calls for more and better establishment-level data increase Schneider, 2013;Dock et al, 2015), including socioeconomic and -demographic information about the transportation system users, it is critical to include these data to increase our understanding of trip generation. Table B19013; 2 2010 Census, Summary File 1 (SF1), Table P2; 3 2013 ACS, 5-year summary, Table B17010; 4 2010 Census, SF1, Table H13; 5 2013 ACS, 5-year summary, Table B99051; 6 2010 ACS, 5-year summary, Table B25044 4…”
Section: People Mattermentioning
confidence: 99%
“…In a 2013 study, Schneider (2013) surveyed visitors to shopping districts in suburban and urban areas and found that 65% of trips between land uses in all shopping districts were walking trips, but in urban centers, approximately 96% of trips between land uses were walking trips. Furthermore, we have only begun to understand the ways in which trips are captured within mixed-use buildings (e.g., Walters, Bochner, & Ewing, 2013), but the available methods have not been adequately tested with a range of contexts.…”
Section: Internal Capture In Existing Neighborhoodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intercept survey is a widely accepted data collection method used by researchers throughout the world (Behrens and Schalekamp, 2010;Grov et al, 2007;Kate and Konstadinos, 2009;Schneider, 2013). According to Cripwell et al (2009), an intercept survey is performed by survey staff at a particular location by approaching potential participants when they enter or exit that particular location.…”
Section: Intercept Surveymentioning
confidence: 99%
“…People who travel from one place to another for their daily purposes by walking cover 1.25km per trip. Average travel speed in Dhaka is 15.2km per hour, which comes down to 10/12km per hour during traffic congestion (Schneider, 2013). Grov et al (2007) Evidence shows that the travel time of buses varies.…”
Section: Travel Distance Speed and Timementioning
confidence: 99%